FORMULATION OF FLUCONAZOLE AS TOPICAL ANTIFUNGAL GELS BY MICROSPONGE BASED DELIVERY SYSTEMS - Swamykannu Dinesh Mohan; Vangadari Rama Mohan Gupta (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
The purpose of present work was to formulate Fluconazole loaded microsponge-based topical delivery system for modified release. Microsponges with varied drug–polymer ratios were prepared by emulsion solvent diffusion technique using Ethyl cellulose as release retard material. Prepared microsponges were studied for particle size and physical characterization. Scanning electron microscopy (SEM) images showed the microsponges porous and spherical in shape. The microsponges were then incorporated in carbopol gel and evaluated for pH, viscosity, spreadability, drug content, in-vitro release. The In vitro drug release showed that microsponges with 1:1.5 drug–polymer ratios (F3) were more efficient to give sustained release of 74.2% at the end of 8 hr. All the microsponge gel formulations (i.e.F1- F10) showed better results like pH between 6.5-7.0, viscosity between 25,030-47,390 cps, spreadability 2-4 cm/s and drug content of 76.20±0.02% to 96.41±0.01%. Hence, the fabricated microsponge based formulation of Fluconazole would be anticipation and promising substitute to conventional therapy of skin infections.